Integrated Trajectory Planning and Sloshing Suppression for Three-Dimensional Motion of Liquid Container Transfer Robot Arm. (18th May 2015) - Aribowo, Wisnu; Yamashita, Takahito; Terashima, Kazuhiko
Abstract : For liquid transfer system in three-dimensional space, the use of multijoint robot arm provides much flexibility. To realize quick point-to-point motion with minimal sloshing in such system, we propose an integrated framework of trajectory planning and sloshing suppression. The robot motion is decomposed into translational motion of the robot wrist and rotational motion of the robot hand to ensure the upright orientation of the liquid container. The trajectory planning for the translational motion is based on cubic spline optimization with free via points that produces smooth trajectory in joint space while it still allows obstacle avoidance in task space. Input shaping technique is applied in the task space to suppress the motion induced sloshing, which is modeled as spherical pendulum with moving support. It has been found through simulations and experiments that the proposed approach is effective in generating quick motion with low amount of sloshing.